Pengaruh Pemasaran Eksperimental dan Pemasaran Kerelasian Pelanggan terhadap Nilai Pelanggan serta Implikasinya Terhadap Loyalitas Pelanggan Hotel - Ananta Budhi Danurdara (Kontigensi : Jurnal Ilmiah Manajemen, 2016)
The research objective is to get empirical evidence and found the clarity of the phenomenon, as well as the conclusion about experiential marketing implementation, Marketing Customers Relationship in creating customer value it’s Implications towards customer loyalty at star hotel of 3, 4 and 5 in the city of Bandung and West Bandung Regency. The results are expected to benefit from the practical terms and also contributed to the development of management science, especially marketing management. This study uses a quantitative approach with descriptive inductive method, namely collecting, presenting, analyzing, and testing hypotheses, and to develop conclusions and suggestions. Results showed the application of experiential marketing according to the perception of new customers included in the category quite well; the application of customer relationship marketing in both categories; the application of customer value under the category quite well; customer loyalty under the category of pretty loyal; marketing experiential marketing and customer relationship significantly affect customer value star hotel in the city of Bandung and West Bandung regency. Results of the study confirmed the importance of experiential marketing implementation and marketing customer’s relationship because it can increase customer value, which also has implications for customer loyalty star hotel in the city of Bandung and West Bandung regency.